KONSEP DAN PERANAN PENDIDIK DALAM PERSPEKTIF ISLAM - emawati emawati; Diana (Kalam: Jurnal Agama dan Sosial Humaniora, 2021)
Educators have been limitedly defined as teachers and lecturers who teach in formal institutions. This notion of educators, however, needs to be conceptualized to identify the true nature of educators. This particular manuscript explores concepts of educators from various literature to come up with the true nature of educators. This is library research, in which various literature on the nature of educators are explored and reviewed using content analysis strategy. The findings suggest that educator is not defined in limited notion, in which teachers and lecturers are only educators recognized. Educators are not limited to those whose formal accupation is teaching or lecturers in formal education institutions. There are various levels of educators: the first and the foremost known educator is Allah SWT, the almighty God as He teaches human being through revealation; the second educator in the Islamic literature refers to the Prophet Muhammad PbuH. Through his teaching Muslims recognize Islam and its teaching. Parents and teachers are the next two types of educators as found in our analysis of literature. This article also identifies several attributes of teachers according to Islamic literature, one of which is faithful to Allah, have strong characters, knowledgeable and communicative